PENGARUH KEPEMILIKAN INSIDER DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA: A PIECEWISE LINEAR REGRESSION ANALYSIS - Faisal . (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2013)
This study aims to examine the impact of insider ownership and debt policy on firm value at manufacture industries in Indonesia Stock Exchange. The issue arises as to whether these ownership structure and debt policy have been effective in reducing agency costs, and therefore enhancing firm value. This paper utilizes a panel data analysis of 293 firm years listed in the Indonesia Stock Market over a seven years period from years 2002 to 2008. A piecewise linear regression model is used to test the hypotheses. Overall, the results highlight the importance of ownership structure role played by insider ownership and debt policy with three control variabels to influence firm value. We find a nonmonotonic relation between the fraction of common stock owned by insider and firm value. We find that the negative entrenchment effect is dominant when insider ownership level is less than 5% or greater than 25%, while the 5% to 25% insider ownership level reflect the convergence of interest ( alignment ofinterests ) hypothesis. We also find a significant positif relation between debt policy and firm value. Finaly, we also find that firm size, firm profitability, and firm age as control variabels have significant impact on firm value. The results are consistent with the hypothesis that firm value is a function of the structure of equity ownership, and debt policy.Keywords: insider ownership, debt policy, agency cost, and firm value